The Formation of a Religious Society Through Dynastic Leadership - Idrus, Moh. Syafi'i; Wahid, Abdul; Singh, Irom Gambhir; Jannah, S. Fathiyatul; Bashori, Abdul Hamid (Al Irsyad: Jurnal Studi Islam, 2024)
As a pluralistic society, Indonesia conducts religious and cultural activities, with the village head ensuring the implementation of Islamic law and dynasty leadership that influences stability and power distribution. This study aims to uncover the formation of dynasty leadership, the strategies of the Village Head, and Islamic views on leadership and religious values in Campor Timur Village. The researcher used a qualitative method with a phenomenological approach. Data collection techniques included interviews, observations, and documentation. The researcher conducted condensation, data presentation, and conclusion drawing in data processing. The results show that leadership strategies in forming a religious community involve several steps. First, preaching through lectures, writings, actions, media, and regular study sessions increases religious awareness. Second, the leader collaborates with religiously devout communities and the government to create harmonious relationships. Third, the leader provides facilities such as roads, meeting halls, and mosques to support socio-religious activities and improve the community's quality of life, particularly regarding better access to religious education. In conclusion, effective leadership successfully forms a religious community by strengthening religious values, fostering cooperation, and sustaining facilities that support social and religious activities. Conclusion: Effective leadership shapes a religious community through preaching, cooperation, and providing facilities to support social and religious activities.